LatticeWorks: An open-source MATLAB toolbox for nonuniform, gradient and multi-morphology lattice generation, and analysis - Mahtab Vafaeefar; Kevin M. Moerman; Ted J. Vaughan (Materials & Design)
This study introduces an open-source MATLAB toolbox, LatticeWorks, that offers a versatile platform for generating and analysing lattice structures, facilitating the exploration of nonuniform, functionally graded designs. It encompasses various lattice generation methods, including single- and multi-morphology lattices, linearly graded lattices, different boundary shapes, and cell arrangements (such as cylindrical and spherical). The toolbox also features volume infill lattice generation based on a signed distance function, allowing lattice structures to be applied to arbitrary domains. Other developments include extending transition boundary shapes to cylindrical and spherical coordinates, enhancing cylindrical cell arrangement methods, and introducing tailored density lattice methods for smooth density mapping. Unlike other available packages, LatticeWorks offers inclusive and detailed implementation methods that are integrated with finite element analysis for mechanical property evaluation. The toolbox’s capabilities open new paths for designing complex lattice structures, tailored to specific functional requirements, across diverse applications.